Multimorbidity, healthcare utilization, and quality of life for older patients undergoing surgery: A prospective study - Thanakiattiwibun C. (2023)
Multimorbidity (≥2 chronic illnesses) is a worldwide healthcare challenge. Patients with multimorbidity have a reduced quality of life and higher mortality than healthy patients and use healthcare resources more intensively. This study investigated the prevalence of multimorbidity; examined the effects of multimorbidity on healthcare utilization; healthcare costs of multimorbidity; and compared the associations between the health-related quality of life (HRQoL) of older patients undergoing surgery and multimorbidity, the Charlson Comorbidity Index (CCI), the Simple Frailty Questionnaire (FRAIL), and the American Society of Anesthesiologists (ASA) physical status classifications. This prospective cohort study enrolled 360 patients aged > 65 years scheduled for surgery at a university hospital. Data were collected on their demographics, preoperative medical profiles, healthcare costs, and healthcare utilization (the quantification or description of the use of services, such as the number of preoperative visits, multiple-department consultations, surgery waiting time, and hospital length of stay). Preoperative-assessment data were collected via the CCI, FRAIL questionnaire, and ASA classification. HRQoL was derived using the EQ-5D-5L questionnaire. The 360 patients had a mean age of 73.9 ± 6.6 years, and 37.8% were men. Multimorbidity was found in 285 (79%) patients. The presence of multimorbidity had a significant effect on healthcare utilization (≥2 preoperative visits and consultations with ≥2 departments). However, there was no significant difference in healthcare costs between patients with and without multimorbidity. At the 3-month postoperative, patients without multimorbidity had significantly higher scores for HRQoL compared to those with multimorbidity (HRQoL = 1.00 vs 0.96; P <.007). While, patients with ASA Class > 2 had a significantly lower median HRQoL than patients with ASA Class ≤2 at postoperative day 5 (HRQoL = 0.76; P =.018), 1-month (HRQoL = 0.90; P =.001), and 3-months (HRQoL = 0.96; P <.001) postoperatively. Multimorbidity was associated with a significant increase in the healthcare utilization of the number of preoperative visits and a greater need for multiple-department consultations. In addition, multimorbidity resulted in a reduced HRQoL during hospital admission and 3-months postoperatively. In particular, the ASA classification > 2 apparently reduced postoperative HRQoL at day 5, 1-month, and 3-months lower than the ASA classification ≤2.